İnşaat sigortası sözleşmesi - Akçar, Nihan (My University, 2004)
Yeni inşaat yöntemlerinin bulunması, planlamanın gün geçtikçe daha da önem kazanması ve buna istinaden yapı malzemelerinin çeşitlenerek inşaatlarda kullanılması, inşaat süresinin önem kazanarak rekabet sebebi olması, ihale yapılırken paraları garanti altına alınması amacıyla inşaat sigortasına ihtiyaç duymuş ve inşaat sigortası kavramı doğmuştur. İnşaat sigortası sözleşmesinin tarafları sigorta şirketi ve sigorta ettirendir. İnşaat sigortası TTK.' da düzenlenmemiş olup İSPGŞ ile tarafların hak ve yükümlülüklerine ilişkin esaslar belirlenmiştir. İnşaat sigortası sözleşmelerinde tarafların birbirlerine karşı olan bir takım borçları ve mükellefiyetleri mevcuttur. Sigorta ettirenin; prim ödeme, ihbar, koruma tedbirleri alma, malın muayenesine izin verme mükellefiyeti söz konusudur. Sigortacının; sigorta poliçesini teslim, tazminat ödeme, sır saklama mükellefiyeti bulunmaktadır. İnşaat sigortasını sona erdiren sebepler çeşitlilik arz etmektedir. Sigorta sözleşmesinin süresinin bitimi, rizikonun gerçekleşmesi veya sigorta sözleşmesinin devamı sırasında rizikonun gerçekleşme imkanın kalmaması, tarafların anlaşması, taraflardan birinin fesih hakkını kullanması vs bu sebeplerdendir. İnşaat sigortası sözleşmesinden doğan bütün talepler iki yıllık zamanaşımı süresine tâbidir. Günümüzde gelişen ve değişen ihtiyaçlar karşısında inşaat sigortası sözleşmesinin başlı başına bağımsız bir kurum olarak kendine özgü ve mahiyetine uygun bir şekilde düzenlenmesinin inşaat sigortası kavramının daha açık ve net bir biçimde ortaya konması yönünden gerekli olduğu kanaatindeyiz. Development of new construction methodologies, granting priority to the planning from day to day and increase in the variety of the building materials used in the construction, by the importance given to the construction period, its appearance as a competition cause, the necessity to require a construction all risk insurance during the tendering stage to secure the funds has arisen and consequently the construction insurance concept has occurred. The parties to the construction insurance agreement are the insurance broker and the insured. The construction insurance is not in force in the Turkish Trade Law, however, in the General Conditions of Construction Insurance Policies the principles of the rights and responsibilities of the parties are determined. Within the provisions of the construction insurance agreement the responsibilities of the parties against each other are defined. The insured is responsible to pay the insurance premium, to denounce, to ensure the application of protection measures and to allow inspection to the property, whereas the insurance company is responsible to deliver the insurance policy, to pay indemnity and to keep the information confidential. The reasons that permit the termination of the construction insurance shows variety. The expiry period of the insurance agreement depends on the occurrence of the risk or within the term of the insurance agreement removal of the possibility of the occurrence of the risk, the mutual agreement of the parties or application of the termination right of one of the parties. All the claims under construction insurance agreement have a prescription period of two years. We are confident that against the continuous developing and changing necessities of the present times, issuance of the construction insurance agreement through an independent entity in an appropriate way is a requirement to expose the construction insurance concept in an open and clear manner.
Keywords: Özel Hukuk